Factors associated with preventive health services use by older war-displaced Japanese returning from China and by older Korean residents of Japan: a descriptive correlational study - Chu Hyang Oh (BMC Health Services Research)
Abstract Background Among the people with diverse backgrounds and cultural customs living in Japan, two important groups, namely, war-displaced Japanese returning from China and South and North Korean nationals who are naturalized citizens residing in Japan, will experience population aging in the same way as the general Japanese population. In old age, physical function generally declines, multiple diseases are more likely to occur, and health issues that need to be addressed increase in number. The aim of this study was to identify the factors associated with the use of preventive health services in Japan by older Korean residents and war-displaced Japanese returning from China. Methods The study conducted a cross-sectional study in Japan using a self-administered questionnaire. Respondents comprised 754 people aged 65 or over, including 220 Japanese, 200 war-displaced Japanese returnees from China, and 334 Korean residents of Japan. The behavioral model of health services use served as the analytical framework. Questionnaire items were based on predisposing factors, enabling factors, and need factors. Logistic regression analysis was used to examine the relationship between preventive health services use and each factor. Results The results of the logistic regression analysis showed that being ethnically a war-displaced Japanese returning from China (OR = 0.04; 95% CI [0.00, 0.74]) and being ethnically Korean residents of Japan (OR = 0.13; 95% CI [0.03, 0.62]) were associated with the use of preventive health services. Conclusions The use of preventive health services by older people in Japan is influenced by ethnicity. For these reasons, war-displaced Japanese returning from China and Korean residents of Japan need support to encourage their greater use of preventive health services.